(untitled) (Research, Society and Development, 2023)
Ischemic heart disease is a disease that is caused by a narrowing of the coronary arteries by fatty plaques, causing a reduction in blood flow from the blood to the heart, which can lead to myocardial ischemia or even a heart attack. Objective: This study aimed to analyze the benefits of physical exercises for the prevention and recovery of cardiovascular diseases. Methodology: This is an integrative review study whose survey of works for analysis was carried out through searches in the databases Portal de Periódicos CAPES, Scientific Electronic Library Online - Scielo, PubMed. Results: After the systematic selection of studies, seven studies were listed for the final sample. The study showed that the practice of physical exercise, be it in a resisted way with high loads or aerobically with low loads, brings significant improvements for individuals both in the treatment of cardiovascular diseases and in the prevention to avoid obtaining the same benefits in the future. those that are the increase of strength and endurance of individuals, improvement in aerobic capacity, reduction of body fat that helps internally in improving blood flow, reduction of both systolic and diastolic blood pressure, triglycerides, uric acid and heart rate. Conclusions: The practice of exercises promotes improvements in fat reduction, BMI, improvement in functional capacity, strength, resistance, among others, generally affecting the quality of life of individuals.